Zonas de sobreposición en las en las areas de distribución geográfica de las especies mexicanas de Dendroctonus Erichson (Coleoptera: Scolytidae) y sus implicaciones ecológico-evolutivas - Zúñiga, Gerardo; Mendoza Correa, Guadalupe; Cisneros, Ramón; Salinas Moreno, Yolanda (Instituto de Ecología, A.C., 1999)
Species of Dendroctonus are parasites of conifer forests (Pinaceae-Coniferales), their distribution range being associated with these forest communities. Natural co-existence of Dendroctonus species with ecological, morphological, and reproductiva differences is common; however, observations made in natural conditions suggest the co-existence, in time and space, of some species with similar biological features. The purpose of the present work was tó determine overlapping zones in the distribution range of Dendroctonus species in México. Our study was based on records of specimenes depositad in the main national entomological collections. Maps of distribution range of the species were made per State, which were the basis to determine overlapping zones by the propinquity method. The results show the presence of 27 overlapping zones of two to five species, where latitude, altitude, and host are similar. The presence of these zones suggests that co-existence of Dendroctonus species with similar biological attributes is common, and should be considered in the control of these insects. Additionally, ecological and evolutionary several aspects could be studied in these areas.